Spatial and sociodemographic correlates of gambling participation and disorder among female Filipino migrant workers in Macao, People's Republic of China. (October 2019) - Yi, Grace; Huang, Lei; Lam, Agnes I.F.; Latkin, Carl; Hall, Brian J.
Abstract: Background and aims: Correlates and risk factors for gambling disorder among vulnerable or transient populations such as transnational migrant workers are unknown. The current study examined sociodemographic and spatial correlates of gambling disorder among female Filipino domestic workers in Macao (SAR), China. Design: Survey-based, respondent-driven sampling study administered from November 2016 to August 2017. Setting: Macao (SAR), which encompassed 38 casinos within its 30.4 km 2 area at the time of this study. Participants: Representative sample of N = 1194 female Filipino domestic workers in Macao. Measurements: Symptoms of gambling disorder based on Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Correlates evaluated included sociodemographic information, proximity to venues, perceived social support, and symptoms of depression and anxiety. Findings: Prevalence of gambling disorder was 5.1%. Multivariable regression analyses indicated that likelihood of gambling participation (i.e., ever gambling) was associated with current indebtedness (RR = 1.56, 95%CI = 1.08–2.25, p = . 017) and worse self-reported health (RR = 1.31, 95%CI = 1.04–1.65, p = .02). Increased symptoms of gambling disorder were independently associated with lower perceived social support (RR = 0.92, 95%CI = 0.87–0.98, p = . 006), increased dependents relying upon monthly remittances (RR = 1.10, 95%CI = 1.06–1.16, p < .001), increased depression severity (RR = 1.16, 95%CI = 1.07–1.25, p < . 001), decreased salary quintile (RR = 0.97, 95%CI = 0.94–1.00, p = .04), and proximity to the nearest Mocha Club gaming venues (RR = 1.04, 95%CI = 1.02–1.07, p = .005). The association between proximity to casinos and increased symptoms of gambling disorder was significant only for domestic workers living apart from employers (RR = 1.07, 95%CI = 1.00–1.14, p = .04). Conclusions: Increased spatial proximity to gambling venues and greater financial and psychosocial burdens are associated with gambling disorder among domestic workers in Macao. Highlights: Household spatial proximity to casinos was associated with gambling disorder. Proximity was only associated with gambling among migrants not living with employers. Gambling disorder was associated with debt adversity and lower perceived social support. Migrant workers were nearly two times higher prevalence of gambling compared to locals.